The implementation of mobile internet protocol in local area network - Fisal, Norsheila; Lee, Soon Ho; Mohamed, Yazid (2000)
Mobile Internet Protocol (IP) is a new recommended Internet protocol designed to support the mobility of a user. Host mobility is becoming important because of the recent blossoming of laptop computen and the high desire to have continuous network connectivity anywhere the host happens to be. This paper is concerning the implementation of Mobile IP in local area network (LAN).